2023
DOI: 10.3389/fnmol.2023.1112927
|View full text |Cite
|
Sign up to set email alerts
|

Identification of nicotine-seeking and avoiding larval zebrafish using a new three-choice behavioral assay

Abstract: IntroductionNicotine dependence is one of the main causes of preventable diseases in the United States. Nicotine-seeking and avoidance behavioral assays in larval zebrafish could be used for identifying potential new pharmacotherapeutics in an early phase of drug discovery and could facilitate the identification of genes and genomic variations associated with nicotine-seeking and avoidance behavior.MethodsA new three-choice behavioral assay has been developed for the identification of nicotine-seeking and avoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
(70 reference statements)
0
0
0
Order By: Relevance
“…These biphasic responses have been reported for locomotor activity following embryonic exposure to alcohol [129], nicotine [130] and cannabinoids [131]. They have also been reported in other behavioral tests, with embryonic exposure to nicotine causing an increase in seeking behavior at a low concentration while producing nicotine avoidance at a high concentration [132]. Since zebrafish have another major advantage of allowing behaviors to be tested very early in development, further studies at just 5 days after fertilization have shown nicotine to increase anxiety-like behavior while reducing habituation to an acoustic startle stimulus [133,134] and have shown cannabinoids to have a similar effect on this startle response [135].…”
Section: Behavioral Disturbances Observed In Zebrafish Studiessupporting
confidence: 59%
“…These biphasic responses have been reported for locomotor activity following embryonic exposure to alcohol [129], nicotine [130] and cannabinoids [131]. They have also been reported in other behavioral tests, with embryonic exposure to nicotine causing an increase in seeking behavior at a low concentration while producing nicotine avoidance at a high concentration [132]. Since zebrafish have another major advantage of allowing behaviors to be tested very early in development, further studies at just 5 days after fertilization have shown nicotine to increase anxiety-like behavior while reducing habituation to an acoustic startle stimulus [133,134] and have shown cannabinoids to have a similar effect on this startle response [135].…”
Section: Behavioral Disturbances Observed In Zebrafish Studiessupporting
confidence: 59%